Effect of Specimen Shape on Bond Strength Between Deformed Steel Rebars and Normal Concrete - Majain, Nelly (International Journal of Integrated Engineering, 2025)
The study of the bond between deformed steel rebar and concrete is essential in reinforced concrete structures, considering the assumption that rebar and concrete function as composite materials. Over the years, researchers have carried out bond testing, typically using the most common types of specimens, which are cube and cylinder specimens. Despite these advancements, an observation reveals the absence of studies exploring the effect of specimen shape on bond strength. Therefore, this study attempts to investigate the influence of specimen shape on the bond strength between rebar and normal concrete. The experimental work involves the preparation of cube pullout specimens measuring 200 mm x 200 mm x 200 mm, embedded with 16 mm and 20 mm rebars. The cube pullout specimens were then subjected to direct pullout testing using the RILEM pullout test standard. Subsequently, comparisons were made with previous experimental results employing cylindrical pullout specimens (100 mm diameter x 200 mm height), which were obtained by another researcher. The bond strength analysis uses normalised bond strength to minimise the effect of variations in concrete compressive strength. The results of the analysis indicate that bond strength is affected by the thickness of the concrete cover, which is influenced by the shape of the specimens.